2022
DOI: 10.1039/d2sc01872a
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of TiO2/C nanosheets with a directional cascade carrier transfer

Abstract: Directed transfer of carriers, akin to excited charges in photosynthesis, in semiconductors by structure design is challenging. Here, TiO2 nanosheets with interlayered sp2 carbon and titanium vacancies are obtained by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…7,8 In this regard, a cascade system, in which inside-out directed transfer of carriers takes place, is desirable to avoid random transport of charge carriers and improve charge transfer efficiency. 9–11 In the context of TiO 2 , one-dimensional (1D) nanostructures such as nanofibers 12,13 and nanotubes 14,15 have been found to have elevated charge collection efficiencies owing to the occurrence of directional charge transport along the longitudinal direction and heightened lifetimes of photogenerated electrons. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In this regard, a cascade system, in which inside-out directed transfer of carriers takes place, is desirable to avoid random transport of charge carriers and improve charge transfer efficiency. 9–11 In the context of TiO 2 , one-dimensional (1D) nanostructures such as nanofibers 12,13 and nanotubes 14,15 have been found to have elevated charge collection efficiencies owing to the occurrence of directional charge transport along the longitudinal direction and heightened lifetimes of photogenerated electrons. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In addition, it has also been confirmed that the PCC transfer at a single nanocrystal is usually random, so that the great majority of PCCs are recombined and dissipated before reaching the surface of semiconductors, and only those PCCs that diffuse to the surface of photocatalysts can be used for the photochemical reactions. 5 Therefore, in order to promote the fast transfer and efficient utilization of PCCs, directional transfer of PCCs was proposed owing to a minimum of energy-loss and a maximum of energy-utilization, such as building heterojunctions or phase junctions, creating impurities/defects as electron trap centers, constructing nanoarchitectures or crystal-facet engineering, etc. 6,7 By contrast, the nanostructural design of heterojunction photocatalysts is a more common strategy for accelerating the directional transfer of PCCs under the effect of an interfacial built-in electric field.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, surface engineering of TiO 2 by constructing composites with nanometals, nanocarbon, and impurities has been widely used for enhancing the performance of TiO 2 photocatalysts. [6][7][8] Significant progress has been made with a growing understanding of photocatalytic mechanisms on the TiO 2 surface at the atomic scale. [9][10][11][12] Directional transfer of carriers to the surface can minimize energy losses and thus is mostly preferred.…”
Section: Introductionmentioning
confidence: 99%